PENINGKATAN KESADARAN HUKUM MENGENAI HAK DAN KEWAJIBAN WARGA NEGARA BAGI PAGUYUBAN ISTRI PEDULI DI DESA MEKARJAYA, INDRAMAYU - Zaelani, Ahmad; Rahmadona, Anisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Legal awareness is the values that exist within humans regarding the law that is expected to exist. Legal awareness regarding rights and obligations is important to be internalized by every citizen. The low level of understanding regarding the rights and obligations of citizens in society indicates a lack of legal socialization. This study aims to increase legal awareness among members of the concerned wives' association in Mekarjaya Village, Indramayu, regarding the rights and obligations of citizens. It uses an empirical legal method, namely legal research that examines the factual implementation of positive legal provisions (legislation) in specific legal events that occur in society. It uses a descriptive qualitative approach, where data is collected through field observation techniques. The results of the pre-test showed that most participants (60%) failed to correctly answer questions regarding the substance of Article 31 of the 1945 Constitution on the right to education. Through a qualitative descriptive approach, which simplified the articles of the constitution into everyday language, there was an increase in scores from an average of 52 in the pre-test to 75 in the post-test. This shows an increase in participants' legal awareness and understanding of the rights and obligations of citizens.